Realism and educational research : new perspectives and possibilities - Scott, David, 1951- (Social research and educational studies series ;, 2000)
Although the literature of social research covers a vast range of material, there has been little on the role of social theory in educational research. In this respect, David Scott's book covers an important gap in the market, as it focuses on the centrality of social theory in a variety of empirical projects. The volume covers a range of conceptual and theoretical discussions and subsequently applies these concepts to our analysis of empirical studies. As a consequence, it is a volume that deserves to be read widely by students and researchers alike.